The making of the people in 2 Maccabees 3 in the Heliodorus scene - Jordaan, Pierre J. (HTS teologiese studies, 2023)
The view of the deity and the people in 2 Maccabees seems to be a dynamic rather than a stagnant relationship. On the one hand, the deity sometimes punishes his people through the enemy. However, in other instances, he defends them against the same enemy. In this sequence of events, the ‘Heliodorus scene’ in 2 Maccabees 3 is quite unique. A protagonist and his helpers (a man on a horse and two youths) as well as an antagonist and his helpers (Heliodorus and his bodyguard) can be shown. Minor, seemingly insignificant players – the ‘widows and orphans’ – are also found. Doran states that mentioning them in this scene is possibly a rhetorical ploy and refers to LXX Psalms 67:6 (Ps 68:5) as possible background. However, Doran, unfortunately, does not investigate LXX Psalms 67 further. Upon closer inquiry, this text might show an interesting context for the Heliodorus scene and the making of the people. It demonstrates how ‘the people’ should conduct themselves, the role of the sanctuary, and if one can expect the deity to get involved.Contribution: This is a new contribution as the relationship between LXX Psalms 67 and 2 Maccabees 3 has never been looked at in this way.